Community Development Education: Examining Students’ Video-Based Case Analysis on Community Issues, Indigenous Ethnic Protection and Empowerment - Suryani, Adi; Soedarso, Soedarso; Wahyuddin, Wahyuddin; Saifulloh, Moh; Zahrok, Siti (Universitas Pendidikan Indonesia, 2020)
One of many development efforts is increasing today students development issues care and awareness. They are going to be the future nation developers and leaders. Thus, it is significant to promote understanding on various community development issues and stimulate their analytical thinking and problem solving. Video is one of many educational means to assist students’ learning process. It provides authentic materials and feeling experience of being there, instead of bringing the students to the real hazardous jungle. This study aims to analyze student-participants analysis on Dayak indigenous community issues and problem solving stimulation using a case study video. Qualitative research method is employed to achieve the research objectives. Thirty-five students are participating in the study. The studentparticipants written responses are analyzed by classifying them into emerging themes and categories, interpreting the underlying meaning and linking to the findings of existing projects, researches, and projects on development. The study reveals that the student-participants propose four main solutions. Those are environment and culture care, external development agents inclusion, capacity building and adaptive capacity development.